Momentum imaging of doubly charged ions of Ne and Ar in the sequential ionization region - Maharjan, C. M.; Alnaser, A. S.; Tong, X. M.; Ulrich, B.; Ranitovic, P.; Ghimire, S.; Chang, Z.; Litvinyuk, I. V.; Cocke, C. L. (My University, 2005)
We have measured with high resolution the full vector momenta of the doubly charged recoil ions produced when Ar and Ne atomic targets are ionized by intense circularly polarized few-cycle (∼8fs) laser pulses in the sequential ionization region. The momentum spectra of the ions were found to exhibit structure which is characteristic of the relative binding energies of the two electrons and the sequential nature of the emission process. We demonstrate that the measured spectra can be used to extract subcycle time information regarding the sequential release of the two electrons.